Emergence - Greve, Henrich R.; Seidel, Marc-David (Emerald Publishing Limited, 2017)
The recent growth in research on the topic of evolutionary novelties inspired this volume of Research in the Sociology of Organizations. While previous sociological work has done an admirable job of understanding selection and differentiation processes, it has widely ignored the origin of novelty and how it grows to form initial structures and practices. Emergence is an easy to understand intuitive concept, as it simply means that an object comes into existence or appearance, but it needs further unpacking as a description of a widespread social process. In this book, emergence is seen as a process that involves 1) the creation of novelty, 2) its growth to a salient size, and 3) its formation into a recognizable social object, process, or structure. Each step should be understood through theory and empirical work. Yet the theory of each step can differ from, though it may be related to, the theory of the other two. As a consequence, emergence is a much more complex research topic than is suggested by a single word and it is these complexities that are examined in this book.- Resué vydavatel
Obsahuje index.
Keywords: sociologie organizace; organizační chování; organizational behavior; organizational sociology; sborníky; elektronické knihy; papers of several authors; electronic books